Job Satisfaction of Dietetic Practitioners in Fars Province, Southern Iran, 2012 - Afsane Ahmadi; maryam ranjbar zahedani; Mahsa Moazen; Mohammad Hassan Eftekhari; Sareh Keshavarzi (Shiraz University of Medical Sciences, 2014)
Background: Job satisfaction is an emotional and positive feeling which results from job assessment or experiences. It is always considered as a problem in some organizations. Despite the important role of nutrition therapy in patients care, dietitians' job satisfaction is less taken into account. The aim of the present study was to determine the amount of job satisfaction among dietitians in Fars province, Iran.Methods: In this study, job satisfaction of 95 dietitians was evaluated through demographic and job satisfaction questionnaires. They were sent by e-mail or face-to-face referral for participants. Job satisfaction level was classified into 6 different categories including very satisfied, fairly satisfied, slightly satisfied, slightly dissatisfied, fairly dissatisfied and very dissatisfied. The data were analyzed by SPSS software using independent sample t-test, oneway ANOVA and Pearson correlation test. Statistical differences were considered significant at P<0.05.Results: The results showed that 72.6% of the participants were satisfied with their job condition but 27.4% were dissatisfied. The mean score of job satisfaction of dietitians was 57%±10.54 (from the maximum score of 100), indicating the participants 'slight satisfaction. Moreover, the highest and lowest scores were related to the nature of work and salary, respectively.Conclusion: Since the level of job satisfaction affects other institutional variables such as efficiency, motivation, performance, absenteeism or burning out, it is suggested that authorities of Health Ministry provide a condition in which job satisfaction is increased by applying appropriate techniques.